Investigating the Factors Influencing Tax Compliance in Online Transaction: An Empirical Study on MSMEs - Eko Lasmono; Dekar Urumsah (The Indonesian Journal of Accounting Research, 2022)
This study aims to analyze the factors that influence personal tax compliance in paying the income tax from online sales of SMSE, namely tax policy, tax knowledge, tax sanctions, and tax incentives. This study adopted the attribution theory and used a quantitative approach employing a survey method by distributing the questionnaires related to paying online sales tax to the individual taxpayers of MSMEs. A total of 159 respondent data across Yogyakarta, Central Java, and Lampung who met the criteria were analyzed and tested using Structural Equation Modeling (SEM) with the help of smartPLS 3.0. The results of this study indicate that tax knowledge and tax sanctions have significant effects on tax compliance, but tax policy has no significant effect on tax compliance. Likewise, tax incentives are not able to moderate the relationships between tax policy, tax knowledge, as well as tax sanctions and tax compliance.